THEORETICAL BASES AND POSSIBILITIES OF FORENSIC MICROLOGY - Mirzoyan, Sergey (State and Law, 2020)
The given article aims to analyze the theoretical foundations and possibilities of forensic micrology and discuss the related issues. The article deals with forensic micrology development history, essence and subject, forensic examination objects, its important role and significance in crime detection, organizational and theoretical problems in forensic practice, as well prospects for the development of forensic micrologyusing modern techniques.